Collaborative modelling or participatory modelling? A framework for water resources management. (May 2017) - Basco-Carrera, Laura; Warren, Andrew; van Beek, Eelco; Jonoski, Andreja; Giardino, Alessio
Abstract: Decision Support Systems, and, more recently, participatory and collaborative modelling have emerged as a response to increased focus on stakeholder participation in modelling activities for certain fields like water resources management. Researchers and practitioners frequently use 'buzzwords' such as 'participatory modelling' and 'collaborative modelling'. In some cases, both terms are used interchangeably, largely due to unclear distinction between them in literature. This article draws the line between participatory and collaborative modelling by using levels of participation and cooperation as conditioning dimensions. Based on this methodology, a new generic framework is presented. This framework can help identify determinant features of both modelling approaches currently used in water resources management. It permits analysis of these approaches in terms of context, specific use, information handling, stakeholder involvement, modelling team and means. The article concludes with an application of the framework to a collaborative modelling approach carried out for a groundwater study in the Netherlands. Highlights: Participatory and collaborative modelling as a response to challenges encountered with traditional DSSs and stakeholder engagement methods. Participatory modelling differs from collaborative modelling by considering participation and cooperation as conditioning factors. A generic framework for participatory and collaborative modelling approaches in Water Resources Management is proposed.